KEDUDUKAN PRODUK HUKUM DARI FUNGSI PENGATURAN MAHKAMAH AGUNG DALAM SISTEM PERUNDANG-UNDANGAN NASIONAL - S. Endang Prasetyawati (PRANATA HUKUM, 2019)
ABSTRAK Authority of the Supreme Court in Implementing the Functions of Post-Amendment Arrangements of the 1945 Constitution associated with the current national legislation system will be very meaningful to determine whether the legal products made by the Supreme Court have the power such as legal products made by legislators - other invitations. The problem examined is how is the legal product position from the Supreme Court's regulatory function in the national legislation system? To answer these problems, this study uses a normative juridical method with a legislative approach. Sources of data are generated from the study of laws and regulations, decisions of the Supreme Court, Supreme Court regulations, Supreme Court circular letters and related research literature. The resulting data is qualitative data. The data is processed, analyzed, and presented with analytical descriptive methods. Based on the results of the study, it can be explained that the legal product position of the Supreme Court's regulatory function in the national legislation system consists of the position of the Supreme Court Regulation as a statutory regulation, and the position of the Supreme Court Circular as a policy regulation. The advice given is that in the implementation of the Supreme Court's regulatory functions it needs to be limited so that no arbitrary acts or acts of abuse of authority occur.